HIV stigma and viral load among African-American women receiving treatment for HIV. (15th July 2019) - Kemp, Christopher G.; Lipira, Lauren; Huh, David; Nevin, Paul E.; Turan, Janet M.; Simoni, Jane M.; Cohn, Susan E.; Bahk, Mieoak; Berzins, Baiba; Andrasik, Michele; Mugavero, Michael J.; Rao, Deepa
Abstract : Objective: African-American women are more likely than other women in the United States to experience poor HIV-related health; HIV stigma may contribute to these outcomes. This study assessed the relationship between HIV stigma and viral load, over time, among a sample of African-American women receiving treatment for HIV, and explored social support and depressive symptoms as mediators. Design: Secondary analysis of longitudinal data. Methods: Data came from a randomized trial of an intervention to reduce HIV stigma among African-American women in HIV care in Chicago, Illinois and Birmingham, Alabama. Sociodemographic and psychosocial data were collected at up to six study visits over 14 months. Viral loads were extracted from medical records during the study period. Generalized linear mixed effects models were used to estimate associations among overall, internalized, and enacted HIV stigma and viral load over time. Mediation analyses were used to estimate indirect effects via social support and depressive symptoms. Results: Data from 234 women were analyzed. Overall HIV stigma was significantly associated with subsequent viral load (adjusted β = 0.24, P = 0.005). Both between-subject (adjusted β = 0.74, P < 0.001) and within-subject (adjusted β = 0.34, P = 0.005) differences in enacted stigma were associated with viral load. Neither social support nor depressive symptoms were statistically significant mediators. Conclusion: Ongoing experiences of HIV stigmatization may contribute to increased viral load among African-American women in primary HIV care. Interventions should aim to alleviate the consequences of stigma experienced by patients and prevent future stigmatization. Abstract : Supplemental Digital Content is available in the text